Determinants of Payment Processing Inefficiencies: Qualitative Study of Accounts Payable Aging in Indonesia - Andi Tigor Lubis; Jonathan Nahum Marpaung (Hasanuddin Economics and Business Review, 2025)
This study diagnoses the drivers of accounts payable delays in a multinational manufacturer in Indonesia using a single case design that integrates quantitative Pareto analysis with qualitative Fishbone investigation. We analyse forty-two supplier invoices aged beyond ninety days and conduct six interviews across finance, logistics, and procurement to prioritise causes and explain their mechanisms within legacy ERP conditions, bonded-warehouse logistics, and import-quota controls. Four categories, namely receipt data errors, items still being searched, missing items, and unposted receipts, account for approximately eighty-three per cent of delays and indicate concentrated leverage for improvement. Recommended interventions include competency building and workload balancing, the separation of workflows for goods and service invoices, automated three-way match validations, real-time SLA dashboards, and supply planning that reflects bonded-warehouse constraints. These actions are expected to cut average cycle time by twenty to thirty per cent and raise first-pass match rates to about eighty-five per cent. The study advances evidence-based operations governance for emerging-market manufacturing and informs procurement policy alignment with customs regulation. This manuscript fits the aim and scope of HEBR by translating rigorous analysis into policy-relevant and managerial implications that enhance sustainable business processes in the Asian context.